PENDEKATAN KERUANGAN DALAM KAJIAN PERMUKIMAN GUA - Nurani, Indah Asikin (BRIN, 1997)
As is well known, a cave area is limited, so it is interesting to study more deeply. It is hoped that the limited cave area can be used as a benchmark as a starting point in the study of settlement patterns with an approach through spatial archaeology. So far, research on cave settlement patterns has been carried out in the stage of determining the type of activity of the cave dwellers, which is focused on certain units of analysis such as artifacts and ecofacts contained in the cave. Meanwhile, research on the reconstruction of patterns and ways of life as well as the use of the available cave land has never been carried out. The patterns and models that were carried out and which were known to mankind at that time are interesting to be researched.